2005
DOI: 10.1097/01202412-200505000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Quadricepsplasty in arthrogryposis (amyoplasia): long-term follow-up

Abstract: Eight patients with arthrogryposis multiplex congenita (amyoplasia type) (11 knees) with knee hyperextension deformity underwent quadricepsplasty and were analyzed during an average follow-up period of 11 years and 2 months. The results were clinically analyzed based on gait pattern, range of movement, and orthotic requirements. Joint congruency was evaluated by radiography according to the Leveuf Pais classification. A satisfactory result was the correction of the deformity, articular congruency, sufficient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Quadricepsplasty was performed mostly to correct extension contractures, and in some cases flexion contractures as well (Borowski et al, ; Ho & Karol, ). Fucs et al () and Ghoreishi et al () reported improved knee passive flexion from a preoperative mean of 1.09 and 4.09° to a post‐surgery mean of 67.30 and 70° with final quadriceps strength of grade 4 or 5 after a follow‐up ranging between 2 years and 17.11 years after quadricepsplasty. Other procedures included hamstring and gastrocnemius lengthening, soft‐tissue release and hamstring transfer with no specific results reported for them (Fassier et al, ; Hahn, ; Ho & Karol, ; Van Bosse et al, ; Yang et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Quadricepsplasty was performed mostly to correct extension contractures, and in some cases flexion contractures as well (Borowski et al, ; Ho & Karol, ). Fucs et al () and Ghoreishi et al () reported improved knee passive flexion from a preoperative mean of 1.09 and 4.09° to a post‐surgery mean of 67.30 and 70° with final quadriceps strength of grade 4 or 5 after a follow‐up ranging between 2 years and 17.11 years after quadricepsplasty. Other procedures included hamstring and gastrocnemius lengthening, soft‐tissue release and hamstring transfer with no specific results reported for them (Fassier et al, ; Hahn, ; Ho & Karol, ; Van Bosse et al, ; Yang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Hall et al () reported that among 135 children with Amyoplasia, 87 had knee flexion contractures and 16 had knee extension contractures. Knee dislocations or subluxations were found in eight studies (Bharucha et al, ; Binkiewicz‐Glinska et al, ; Borowski et al, ; Fucs, Svartman, de Assumpcao, & Lima Verde, ; Ghoreishi, BirjandiNejad, & Hallaj Moghadam, ; Kroksmark et al, ; Sud et al, ). Ayadi et al () reported an agenesis of the patella and displacement of the patella was reported in two studies (Binkiewicz‐Glinska et al, ; Borowski et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have not encountered tibial fractures, we have never had to resort to tendon grafting and in no instance did we have to re-operate a child. Restoration of knee motion entailed a very short period of supervised physiotherapy in this series, without having to resort to repeated manipulations under general anaesthesia every 3-4 days, as recommended by Fucs [21]. The overriding advantage of a single-event surgery over repeated general anaesthetics in an infant cannot be over-emphasised.…”
Section: Discussionmentioning
confidence: 99%